2022
DOI: 10.3389/fviro.2022.869657
|View full text |Cite
|
Sign up to set email alerts
|

Using 2D and 3D pluripotent stem cell models to study neurotropic viruses

Abstract: Understanding the impact of viral pathogens on the human central nervous system (CNS) has been challenging due to the lack of viable human CNS models for controlled experiments to determine the causal factors underlying pathogenesis. Human embryonic stem cells (ESCs) and, more recently, cellular reprogramming of adult somatic cells to generate human induced pluripotent stem cells (iPSCs) provide opportunities for directed differentiation to neural cells that can be used to evaluate the impact of known and emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 237 publications
0
1
0
Order By: Relevance
“…Several mechanisms link COVID-19 to nerve damage in PFNP. First, COVID-19's neurotropic nature can directly harm neurons (24), especially peripheral nerves that are more vulnerable than central nerves (25). This is consistent with findings of Khurshid et al ( 16), which showed equal bilateral facial nerve involvement.…”
Section: Discussionsupporting
confidence: 87%
“…Several mechanisms link COVID-19 to nerve damage in PFNP. First, COVID-19's neurotropic nature can directly harm neurons (24), especially peripheral nerves that are more vulnerable than central nerves (25). This is consistent with findings of Khurshid et al ( 16), which showed equal bilateral facial nerve involvement.…”
Section: Discussionsupporting
confidence: 87%
“…Neural stem cells (NSCs) have been proposed as potential tools for research and replacement therapy in neurodegenerative diseases such as AD [ 15 ]. Moreover, the ability to integrate the advantages of stem-cell-based cellular models with genome editing techniques and engineered three-dimensional (3D) microenvironments holds tremendous potential for developing in vitro systems to explore cellular responses to infections that are both relevant and predictive [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%